2011
DOI: 10.4103/2230-973x.82432
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of albumin nanoparticles encapsulating curcumin intended for the treatment of breast cancer

Abstract: Introduction:For the real-time clinical utilization of curcumin (an ayurvedic natural product) to treat breast cancer, its dissolution, rate limited solubility, poor tissue absorption, and extensive in vivo metabolism that leads to its poor systemic bioavailability should be overcome. A polymer-based nanoparticle formulation using bovine serum albumin can increase its aqueous solubility and can achieve protected, sustained, and targeted therapy in breast cancer.Materials and Methods:Desolvation technique was o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
83
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(100 citation statements)
references
References 16 publications
8
83
1
Order By: Relevance
“…Consequently, this enhancement leads to a significant antiproliferative effect (IC 50 ¼ 70 mM) in MDA-MB-231 cells as compared with free curcumin (IC 50 ¼ 90 mM at 72 h). 59 In consistence with that data, Wartlick et al 66 previously reported that the presence of albumin in nano-formulation increased the endocytic uptake and the accumulation of the loaded drug within tumor site.…”
Section: Pathological Bone Environmentmentioning
confidence: 81%
See 3 more Smart Citations
“…Consequently, this enhancement leads to a significant antiproliferative effect (IC 50 ¼ 70 mM) in MDA-MB-231 cells as compared with free curcumin (IC 50 ¼ 90 mM at 72 h). 59 In consistence with that data, Wartlick et al 66 previously reported that the presence of albumin in nano-formulation increased the endocytic uptake and the accumulation of the loaded drug within tumor site.…”
Section: Pathological Bone Environmentmentioning
confidence: 81%
“…57 Pharmacokinetic studies reported that curcumin nano-formulation displayed a larger area under curve (AUC)-time curve as compared with free curcumin. [57][58][59] For example, encapsulation of curcumin by poly(lactic-co-glycolide) (PLGA) nanoparticles provided a significant higher maximal concentration (1000-fold increase) as compared with free curcumin following 60 min of i.v. administration in mice.…”
Section: Pathological Bone Environmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Prominently, these protein nanocarriers possess many surface charge groups which are found to be advantageous in the loading or entrapment of numerous drug molecules. 11 Moreover, the unique ligand delivery property of albumin is found to be advantageous in enhancing the solubility of various hydrophobic drugs combined with serum albumin by loading, entrapment, or conjugation and helps in improving the pharmacokinetics of drug molecules in a biological environment. 9 These unique properties of serum albumin make it an ideal choice for drug delivery applications and development of drug delivery carriers.…”
mentioning
confidence: 99%